Increased Fasting Plasma Glucose and Breast Cancer Risk in Sudanese Women: Association with Premenopausal Status and High Body Mass Index - Ali Osman, Hiba Mahgoub; Faggad, Areeg Saad (Asian Pacific Journal of Cancer Biology, 2022)
Background: Female breast cancer is the most common cancer in Sudan, however little data is available about breast cancer in Sudanese. We aimed to assess whether fasting glucose and insulin levels are associated with the risk of having breast cancer in Sudanese women. Methods: This study was conducted at the National Cancer Institute – University of Gezira (NCI-UG), Sudan. A total of 174 females were enrolled, the patient group included 77 newly diagnosed untreated breast cancer women and a control group of 97 healthy women. Overnight fasting blood samples were collected to measure fasting plasma glucose and serum insulin levels. Results: The fasting plasma glucose level was significantly increased in the breast cancer patients (101.94±2.94 mg/dL) than the controls (90.75±2.02 mg/dL), p=0.002. Overweight-obese and premenopausal breast cancer patient’s subgroups revealed significant elevation of fasting glucose levels (105.35±4.06 mg/dL); (99.64±4.06 mg/dL) compared to controls (89.44±2.62 mg/dL), p=0.001; and (86.38±2.44 mg/dL), p=0.007 respectively. Only in the non-obese patients the insulin level was significantly lower (3.76±0.40 µU/ml) than in the control (6.11±1.00 µU/ml) p=0.034. The patient group was more likely to have 2.5 times higher fasting glucose level than the control (p=0.005). Moreover, the overweight-obese and premenopausal breast cancer patients subgroups were more likely to have 4.4 times and 4.5 times respectively elevated fasting blood glucose level, both with p=0.002. The non-obese breast cancer patients were tended to have 4.3 times decreased insulin level (p=0.019). Conclusion: The elevated fasting plasma glucose levels are associated with high risk of breast cancer in Sudanese women especially in the premenopausal individuals and those having BMI more than or equal to 25 kg/m2. Consequently, adjusting blood glucose level and controlling body weight by changing the lifestyle are suggested to reduce the risk of breast cancer in Sudanese women.